Pengaruh Pelatihan Kewirausahaan, Pemahaman Pemasaran Ritel, dan Pemahaman Undang-Undang Cipta Kerja terhadap Kesiapan Kerja Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Nahdlatul Ulama Lampung - Robi Santoso; Riski Eka Lestari; Reni Diah Setiowati; Fatma Afriyani (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study examines the integrative influence of entrepreneurship training, retail marketing understanding, and the Job Creation Law on the level of work readiness of students at the Faculty of Economics and Business, Nahdlatul Ulama University, Lampung. Quantitative methods were employed, involving 50 respondents selected through probability sampling from a total population of 80 students. The research instrument used an online questionnaire based on a 1-5 Likert scale, analyzed through multiple linear regression with SPSS software. The findings revealed that each independent variable partially exerted a positive and significant influence. Entrepreneurship training contributed a t-value of 3.394 (sig. 0.001), retail marketing understanding recorded a t-value of 3.910 (sig. 0.001), while understanding the Job Creation Law resulted in a t-value of 2.372 (sig. 0.022). Simultaneous analysis showed that all three variables together had a significant effect, with an F-value of 31.451 (sig. 0.001). The research implications confirm that the synergy between entrepreneurial competencies, retail marketing expertise, and employment regulatory literacy forms an essential competency configuration in preparing students to face the challenges of the professional world.